Case Report: Fatal atrioesophageal fistula following atrial fibrillation ablation—critical reflections on prevention - Dai, Qi; Chen, Shutong; Yuan, Ye; Du, Yinghao; Fan, Kuixin; Zhang, Jingfeng; Zheng, Jianjun (Frontiers in Cardiovascular Medicine, 2025)
Radiofrequency ablation (RFA) is an important therapeutic modality for atrial fibrillation (AF), widely utilized in clinical practice due to its safety and significant efficacy. However, post-procedural complications may arise, influenced by anatomical positioning and the intensity of ablation energy, with atrioesophageal fistula (AEF) being particularly rare yet severe. This case report describes a unique instance of a patient developing AEF following AF ablation, accompanied by ischemic stroke and myocardial infarction. A 71-year-old male admitted to the emergency department on July 19, 2024, with acute loss of consciousness and convulsions. Upon admission, physical examination and laboratory tests revealed vital signs within abnormal ranges and indicators suggesting inflammation and potential myocardial injury. Head CT scans showed hypoattenuating areas indicative of cerebral infarction, chest CT suggested possible air accumulation in the left atrial region. ECG findings were consistent with atrial flutter, myocardial infarction, and incomplete right bundle branch block. Given his history of atrial fibrillation and RFA, alongside clinical manifestations, the patient was diagnosed with cardio-cerebral syndrome, suspected to be complicated by an AEF due to the presence of air in the left atrium. AEF diagnosis was confirmed via cardiac CTA, leading to conservative management decisions. Despite initiating thrombolysis for cerebral infarction and supportive treatments for heart failure, including VA-ECMO, the patient's condition continued to decline, evidenced by cardiogenic shock, heart failure, and progressive neurological deficits including coma and dilated non-reactive pupils. Ultimately resulting in family-elected discharge against medical advice on the fourth day of hospitalization.